Implementasi Pajak Karbon Di Indonesia: Potensi Penerimaan Negara Dan Penurunan Jumlah Emisi Karbon - Bintang Adi Pratama; Muhammad Agra Ramadhani; Putri Meiarta Lubis; Amrie Firmansyah (JURNAL PAJAK INDONESIA, 2022)
Implementation of the carbon tax, potential revenue and reducing carbon emissions. Implementing the carbon tax is aimed at changing the behavior of industries to switch to green economic activities that are low in carbon emissions. This study aims to project the impact of the carbon tax in terms of potential revenue and reducing the number of carbon emissions in Indonesia. The research was conducted using qualitative methods with a content analysis approach using carbon emission data from the Ministry of Environment and Forestry and scoping review approach from international literature such as working papers and scientific articles. This study concludes that the Indonesian government can obtain potential carbon tax revenue from the energy sector worth IDR 23,651 trillion in 2025 from the carbon tax imposed. In addition, the results of the imposition of carbon taxes in several countries show that the imposition of carbon tax reduces emissions in those countries.